Ephemerality:Morality:Sovereignty ... - Couzens, Vicki; Guntarik, Olivia (RMIT University, 2024)
BACKGROUND: This portfolio gathers published and exhibited works based on our collaboration as artist and academic. The works problematise the burden of responsibility on Indigenous people having to respond to ongoing forms of colonial violence. We ask: How do we journey towards a permanent sovereignty (of the self) without adding to this burden? This question legitimises the global movement of Indigenous people reasserting their rights. In Australia, First Nations communities are reclaiming knowledge practices as clear articulations of self-determination and sovereignty-never-ceded. Yet few have addressed what it takes to engage non-Indigenous researchers to the decolonising of research in the process of strengthening individual sovereignties. CONTRIBUTION: Ephemerality:Morality:Sovereignty links the theme of temporality to morality and permanency, and questions of sustained ethical engagement to the cause of Indigenous sovereignty. Couzens' contribution as artist challenges the context of ephemerality ...